PIROLISIS LAMBAT CAMPURAN BATUBARA DAN PLASTIK DENGAN KATALIS ZEOLIT ALAM - Wahyu Haryono; Novi Caroko; Thoharudin Thoharudin (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
This research aims to find out the characteristic of slow pyrolysis of coal and plastic mixtures involving natural zeolite as catalyst. Coal was screened in the mesh size of -6 +8 and plastic collected from waste grocery bags were cut in small sizes. Coal and plastic were mixed together in the percentages of 0%, 10%, 20% and 30% of plastic. Coal and plastic mixtures were feeded in the fixedbed pyrolyzer with natural zeolite addition then heated until desired temperature (400oC, 450oC and 500oC) in absence oxygen. The pyrolysis vapor produced from heating was condensed by separated water cooling. The condensation liquid formed was collected and analyzed using GCMS to determain the composition of liquid fraction. This reseach results that the higher temperature pyrolyzer the higher conversion of coal and plastic mixtures is by reducing char product. In addition, by the plastic added in the coal pyrolysis enriches alkane compounds and reduces percentages of PAH compounds. The natural zeolit addition affects in the increase of percentage of alcohol compounds with the alkene compounds reduction